Application Effect of Bladder Function Training Combined with Kangaiping Pills on Permanent Bladder Stoma after Radical Prostatectomy. (24th March 2022) - Sha, Kefu; Zhao, Yue; Yang, Deng; Song, Zhaoxia; Zhao, Mingjun; Gao, Jieqing; Liu, Tiejun
Abstract : Objective . To investigate the application effect of bladder function training combined with Kangaiping pills on permanent bladder stoma after radical prostatectomy (RP). Methods . The clinical data of 80 patients with a permanent bladder stoma after RP in our hospital from December 2018 to December 2019 were retrospectively analyzed, and they were equally split into the experimental group (EG) and control group (CG) according to the odd and even hospitalization numbers. EG received bladder function training combined with Kangaiping pills while CG received routine nursing for permanent bladder stomas to compare the urodynamic indexes and quality of life (QOL) scores after intervention between the two groups. Results . Compared with CG, EG after intervention achieved an obviously higher number of patients with bladder function grade I (∗ ), higher urodynamic indexes (P < 0.001 ), a higher SF-36 score (P < 0.001 ), a lower LUTS score (P < 0.001 ), and a lower total incidence of postoperative adverse reactions (P < 0.05 ). Conclusion . Bladder function training combined with Kangaiping pills is a reliable method to improve the bladder function of patients with a permanent bladder stoma after RP. This intervention method greatly enhances the QOL of patients and reduces the risk of postoperative adverse reactions, which is recommended for clinical application.